Involving Psychometric Tests for Input Device Evaluation with Older People - Mahmud, Murni; Kurniawan, Sri Hastuti (2005)
This paper presents a preliminary study of using psychometric tests when testing input devices with older people. An experiment with twelve older computer users evaluating three commonly use input devices (mouse, touch screen, and tablet-with-stylus) in two common computer tasks (browsing and playing solitaire), proceed by a questionnaire and psychometric tests (Simple Reaction Time,Mini Mental State Exam and Identical Picture), and concluded with debriefing interviews, is described. The paper concludes that psychometric test can provide quantitative data that complement the information collected through the questionnaire and interview and that some psychometric data were the best predictor of task performance.